INVESTIGASI EMPIRIS INTERAKSI FREE CASH FLOW, EARNING MANAGEMENT DAN INEFISIENSI INVESTASI - Djaja Perdana (Universitas Muhammadiyah Malang, 2019)
The level of Free cash flow has a pivotal role for investors to understand the inefficiency of a company's investment. This paper discusses empirical research that investigates the main effects of free cash flow and the effects of their interactions with earning management on investment inefficiency. This study uses a sample of 56 infrastructure, utility and transportation companies registered in Indonesian's Capital Market for the fiscal year ended on December 31, 2014 to 2018. This study uses a multiple regression method with the pooled ordinary least square (OLS) approach for 256 observational data. This study find that the main effect of free cash flow is significantly positive on investment inefficiency, but the earning management does not affect inefficiency investment. Furthermore this study find that the interaction effect of free cash flow is significantly negative on investment inefficiency if the amount of earning management is small.